2021
DOI: 10.5114/pjr.2021.108172
|View full text |Cite
|
Sign up to set email alerts
|

Is chest X-ray severity scoring for COVID-19 pneumonia reliable?

Abstract: IntroductionTo explore whether chest X-ray severity scoring (CX-SS) could be reliable to assess the severity of pulmonary parenchymal disease in COVID-19 patients.Material and methodsThe study consisted of 325 patients whose COVID-19 was confirmed by RT-PCR test and who underwent chest X-ray and computed tomography (CT) studies to assess parenchymal disease severity. Only 195 cases included in the final analysis after exclusion of cases with previous chest disease and cases having more than 24 hours interval b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Our results were concordant with prior studies that reported inter-observer reliability of the severity scoring systems. The inter-reader agreement for CT-SS was excellent in two different studies (ICC median = 0.925, ICC mean = 0.936 and K = 0.85, p = 0.001) [ 10 , 27 ]. Li et al reported excellent inter-observer consistency of the CT visual quantitative analysis with ICC 0.976 (95% CI 0.962–0.985) between 2 observers using only the TSS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results were concordant with prior studies that reported inter-observer reliability of the severity scoring systems. The inter-reader agreement for CT-SS was excellent in two different studies (ICC median = 0.925, ICC mean = 0.936 and K = 0.85, p = 0.001) [ 10 , 27 ]. Li et al reported excellent inter-observer consistency of the CT visual quantitative analysis with ICC 0.976 (95% CI 0.962–0.985) between 2 observers using only the TSS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional chest X-ray proved to have an excellent sensitivity in diagnosing lung involvement in moderate-to-severe COVID-19 cases [ 38 ], and the Brixia scale proved to be the best method to evaluate conventional X-ray chest images during the COVID-19 pandemics [ 10 ]. Maroldi [ 39 ] correlated the A, L and E Brixia scores with the outcomes of COVID-19 pneumonia patients, which makes sense: the lower the Brixia score, the less the lungs were affected upon admission (A score); at the end of hospitalization (E score); and, of course, at the lowest lung involvement (L score).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of pulmonary involvement by COVID‐19 was assessed by chest CT or chest X‐ray. One reviewer with 13 years of experience in thoracic imaging (DB) assessed all chest scans using the total severity score (TSS) 14 to assess the severity in CT scans and (CXR‐SS) or Brixia severity score 15 to assess severity in chest X‐rays. It evaluates the inflammatory abnormalities in each of the five lobes of both lungs, including the presence of ground glass opacities (GGOs), consolidation, or mixed GGOs.…”
Section: Methodsmentioning
confidence: 99%